Keabsahan Perjanjian Jual Beli Satwa Dilindungi dalam Perspektif Hukum Perdata: Studi Kasus Perdagangan Burung di Mojokerto - William Gagas Wicaksana; Ketut Elly Sutrisni; Kadek Januarsa Adi Shudarma; Dewa Krisna Prasada (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The illegal trade of protected wildlife in Indonesia continues to occur, including through digital platforms such as social media and instant messaging applications. This condition raises legal issues, particularly regarding the validity of sale and purchase agreements when the object being traded is prohibited by law. This study aims to examine the validity of agreements involving protected birds from the perspective of Indonesian civil law and to analyze the legal consequences arising from such transactions. The research applies a normative legal method using statutory, conceptual, and case approaches. The findings indicate that although agreements between parties may fulfill elements of consent and capacity, they fail to meet the requirement of a lawful cause as stipulated under Article 1320 of the Indonesian Civil Code. The object of the agreement contradicts Law Number 5 of 1990 concerning the Conservation of Natural Resources and Ecosystems. Consequently, such agreements are considered null and void by law and do not produce binding legal effects. Therefore, civil law does not provide legal protection for transactions involving prohibited objects.